The influence of physiotherapy on blood pressure in children and adolescents with respiratory tract diseases - Pirogowicz, Iwona; Ornat, Maciej; Jerczak, Bartosz; Pachołek, Krzysztof; Domeredzka, Paulina; Gojny, Łukasz (Family Medicine & Primary Care Review, 2017)
Background. Arterial hypertension is an essential, often underestimated medical problem among school youth. Maintaining a low blood pressure (BP) in children should be an important point of pediatric preventive healthcare. Objectives . In our study, we considered the influence of physiotherapy on the blood pressure level in a group of 233 children aged from 8 to 15 years taking part in a rehabilitation camp for children in the Szklarska Poreba mountain resort (95 children in 2014 and 138 children in 2015). Material and methods. The children selected for the study suffered from asthma or recurrent respiratory infections. Measurements were made before and after physiotherapy. During the camp, the children were examined two times in 2014 and three times in 2015. The database created contained 1,208 scores of systolic and diastolic BP. The control group consisted of 50 children whose BP was measured in the same hours, but during the weekend, which was free of physiotherapy. Moreover, the values of heart rate (HR ) during the first measurement were recorded, both in 2014 and 2015. Results. Systolic BP after physiotherapy was significantly lower than before. This result was achieved in every five measuring sessions. In the control group, BP measured in the afternoon was higher than in the morning. The values of HR were not significantly different. The values of BP before and after physiotherapy between children treated with inhaled glucocorticoids and treated without glucocorticoid were not statistically significant. Conclusions . Our studies showed that morning exercise can significantly reduce blood pressure in children throughout the day, even in those who were treated with inhaled glucocorticoids.